A Survey of Waste Management Status in Selected Hospitals in Isfahan - Hiwa Mirzaii; Nasrin Shaarbafchi Zadeh; Farshad Hamidi; Keivan Rahmani; marjan darabi; Akram Ezatifard (Kerman University of Medical Sciences, 2020)
A Survey of Waste Management Status in Selected Hospitals in Isfahan   Mirzaii Hiwa1, Shaarbafchi Zadeh Nasrin2*, Hamidi Farshad3, Rahmani Keyvan4, Darabi Marjan5, Ezatifard Akram5   1. BSc in Health Services Management, Student Research Committee, School of Management and Medical Information Sciences, Isfahan University of Medical Sciences, Isfahan, Iran 2. Assistant Professor in Health Services Management, Health Management and Economics Research Center, Isfahan University of Medical Sciences, Isfahan, Iran 3. MSc Student in Environmental Health Engineering, Department of Environmental Health Engineering, School of Public Health, Tehran University of Medical Sciences, Tehran, Iran 4. Ph.D. Student in Health Services Management, Health Management and Economics Research Center, Isfahan University of Medical Sciences, Isfahan, Iran 5. MSc Student in Health Services Management, Department of Health Management and Economics, School of Public Health, Tehran University of Medical Sciences, Tehran, Iran * Corresponding Author: Nasrin Shaarbafchi Zadeh Address: Hezar Jarib Ave., School of Management and Medical Information Sciences, Isfahan, Iran Tel: 00983137925174                                               Email: nshaarbafchi@gmail.com Abstract: Background & Objectives: The development of various health care facilities has increased the production of medical wastes, which has contributed to environmental pollution and dramatic increase in waste management costs; therefore, the efficient management of hospital waste is of paramount importance. This study aimed to investigate the waste management status of selected hospitals in Isfahan. Methods: This study was cross-sectional and descriptive. In this study, using the checklist provided by Environmental Protection Agency, the data of 14 university hospitals and 1 private hospital were collected. The validity and reliability of the checklist were assessed. Descriptive statistics such as mean and percentage of compliance with the standard were calculated. Results: The average medical waste generated was 379.28 kg / day for each hospital. Moreover, the lowest and highest rates of compliance with standard questions were observed in waste disposal unit (98%) and waste loading (100%), respectively. The studied hospitals performed well in terms of volume and type of waste produced and waste management process. Conclusion: In large hospitals, at-source waste separation is more necessary. Implementing waste management guidelines, procedures, and policies is also crucial, and hospitals need to follow the move from theory to practice to reduce the amount of medical waste and reduce costs.   Keywords: Waste Management, University Hospital, Private Hospital, Medical Waste   Citation: Mirzaii H, Shaarbafchi zadeh N, Hamidi F, Rahmani K, Darabi M, Ezatifard A. A Survey of Waste Management Status in Selected Hospitals in Isfahan. Journal of Health Based Research 2020; 5(4): 343-53. [In Persian]